State strategies in international bargaining : play by the rules or change them? - McKibben, Heather Elko (Cambridge : Cambridge University Press, 2015)
Bargaining between states in the international system is governed by rules, which shape and constrain their bargaining behavior. However, these rules can be changed. When, why, and how do states bargain differently? Drawing on original qualitative and quantitative evidence, this book demonstrates how the rules of the game influence the cooperative or coercive nature of the strategies adopted by all states in a negotiation. These effects influence each state's incentives regarding whether to play by the rules or to change them. Examining these incentives, as well as the conditions under which states can act on them, McKibben explains the wide variation in states' bargaining strategies. Several bargaining interactions are analyzed, including decision-making in the European Union, multilateral trade negotiations, climate change negotiations, and negotiations over the future status of Kosovo. This book provides a rich understanding of the nuances of states' behavior in international bargaining processes.
Introduction : it's a question of strategies -- Typology of bargaining strategies -- How states play by the rules -- When and why states change the rules -- Playing by the rules in European Union negotiations -- Playing by the rules in GATT/WTO negotiations -- Changing the rules in climate change negotiations -- Changing the rules in the Kosovo status process -- Bargaining strategies and beyond.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Diplomatic negotiations in international disputes; International relations; Negotiation; Diplomacy